Trends in Escherichia coli and Klebsiella pneumoniae Urinary Tract Infections and Antibiotic Resistance over a 5-Year Period in Southeastern Gabon - Yann Mouanga-Ndzime; Cyrille Bisseye; Neil-Michel Longo-Pendy; Michelle Bignoumba; Anicet-Clotaire Dikoumba; Richard Onanga (Antibiotics)
Background: Urinary tract infections (UTIs) are a substantial global health concern, exacerbated by the widespread use of antibiotics and leading to the development of multidrug-resistant strains. The aim of this study was to analyze the temporal patterns of Escherichia coli and Klebsiella pneumoniae UTIs and antibiotic resistance, taking into account various sociodemographic, clinical, and climatic factors within the study population. Methods: A total of 3026 urine samples from patients of all ages were analyzed over a period of five years by standard microbiological methods. Climatic data for the study area were also collected. Univariate and multivariate logistic regression analyses were performed to measure the impact of sociodemographic, clinical and climatic parameters on the occurrence of UTIs. Results: The study showed a 31.4% prevalence of UTIs among the population. Notably, there was a significant increase in pyelonephritis between 2019 and 2023 (p < 0.01). Furthermore, a significant association was found between cystitis and the long dry season, as well as the short rainy season. Furthermore, Escherichia coli and Klebsiella pneumoniae exhibited resistance to beta-lactams, quinolones, and co-trimoxazole. The resistance of Escherichia coli isolated from cystitis to nitrofurantoin showed a significant increase over the years (p < 0.04). Principal component analysis (PCA) suggested that humidity may play a role in the emergence of multidrug-resistant strains of Escherichia coli and Klebsiella pneumoniae. Conclusions: UTIs show variability according to various sociodemographic, clinical, and climatic factors, with a higher risk of complications seen in individuals aged ≤ 17 years. It is important to note that cases of pyelonephritis have been increasing over time, with a noticeable seasonal variation. This study suggests that humidity may play a role in promoting antibiotic multidrug resistance in Escherichia coli and Klebsiella pneumoniae.